CARBON EMISSION DISCLOSURE STUDY: STUDY OF OWNERSHIP CONCENTRATION FACTORS WITH THE MEDIATING EFFECT OF CSR DEPARTMENT AND COMPANY AGE - Ngatimin, Ngatimin (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2024)
This study aims to investigate the factors that influence carbon emissions disclosure in mining companies in Indonesia by considering the role of ownership concentration, the existence of a CSR Department, and company age as mediators. Data was collected from audited financial reports of mining companies listed on the Indonesia Stock Exchange during 2017-2021. The analysis method used is Path Regression with the AMOS 23.00 software tool. The research results show that ownership concentration does not significantly affect the disclosure of carbon emissions. This finding is based on agency theory, highlighting interest differences between managers and shareholders. The existence of a CSR Department has a positive and significant influence on carbon emissions disclosure. However, the CSR Department cannot mediate the relationship between ownership concentration and carbon emissions disclosure. Furthermore, company age plays a vital role as a mediator in the relationship between ownership concentration and carbon emissions disclosure, showing that the older the company, the higher the level of carbon emissions disclosure carried out, reflecting experience, deep understanding of stakeholder needs, and commitment company towards sustainable practices.